Inflation Targeting Rules: History-Dependent or Forwarding-Looking? - Kai Leitemo (Norges Bank, 2002)
This paper discusses the optimal use of inflation forecasts in an inflation targeting setting with reaction and implementation lags. It distinguishes between the optimality of history-dependence versus forward-lookingness in monetary policymaking. It is shown that monetary policy strategy is inverted relative to private sector pricing behaviour: if private sector price setting is backward-looking, policy should be forward-looking, and vice versa.
hdl:11250/2498665
Keywords: E52; E61; 330; monetary policy; targeting rule; optimal horizon; history dependence